Study the effect of ewe's pregnancy stages on blood parasitemia of some protozoa infections (Theileria hirci and Anaplasma marginale) and total, differential of white blood cells counts: L.Y. Abd Al-Rhman ,H.M.A. Al-Rubaii , N.W. Zaid - Al-Rhman, L.Y. Abd (The Iraqi Journal of Veterinary Medicine, 2009)
The aim of this study to mentioned the effect of pregnancy on blood parasitemia of some protozoalinfections and total, differential of white blood cells counts from 22 Awassi ewes 3-3.5 years agenaturally infected by Theileria hirci and Anaplasma marginale.Our results showed that there was a positive relationship between the development of pregnancy stagesand the blood parasitemia till reach the highest levels during the last months (fourth and fifth) ofpregnancy of Theileria hirci and Anaplasma marginale 3±0.06%, 2.29±1% and 0.77±0.15%,1.09±0.87% respectively.The total white blood cells count decrease in the first month of pregnancy (5.780±0.54×10³cell/mm³), while increased during the others which reach the highest level in the fourth month ofpregnancy (10.000±0.46×10³ cell/mm³) and then decreased to the lowest level during the lactationmonth (4.920±0.82×10³ cell/mm³) comparison to control group (6.550±0.71×10³ cell/mm³). Neutrophilswere increased during the three months which reach the maximum level during the third month(40±1.98%) and then decreased to the lowest level during the lactation month (25.36±3.46%)comparison to control group (31.46±3.26%). On the other hand, lymphocytes were decreased during thefirst three months to reach the lowest level in the first month (46.8±8.42%) and then return to increasedduring the last tow months of pregnancy to reach to high level in the lactation period (70.79±4.13%)comparison to control group (62.76±3.64%). Monocytes were increased during all pregnancy stages andreach the maximum level in second month (7.4±0.75%) comparison to control group (3.98±0.44%).Same results showed eosinophils except they decreased sharply during the second month (0.8±0.72%)from maximum level in the first month (14.4±4.96%) and slightly decreased during lactation period(1.93±0.56%). Our results showed that the pregnancy stages have a direct effect on blood parasitemia,total and differential counts of white blood cell.